The structure of mentors' behaviour in clinical nursing education: Confirmatory factor analysis. (September 2018) - Chen, Yanhua; Watson, Roger; Hilton, Andrea
Abstract: Aims: To study if a three-factor structure of mentors' behaviour identified through exploratory factor analysis could be confirmed in a dataset assessing mentors' performance using structural equation modelling. Background: To measure mentor's behaviour in clinical nursing education in China, a specific instrument was developed and preliminarily validated; a three-factor structure (professional development, facilitating learning and psychosocial support) was identified in a dataset of assessment of the importance of mentors' each behaviour using exploratory factor analysis and Mokken scale analysis. Design: A cross-sectional study with online and hard copy survey was applied. Methods: Convenience sampling was conducted. Nursing students (n = 634) in Southwest China participated in the study from July to August 2014. Confirmatory factor analysis was used. Results: Mentors' behaviour can be perceived as a secondary order factor with three first order factors: professional development; facilitating learning; and psychosocial support. Conclusion: The three-factor structure of mentors' behaviour was confirmed by structural equation modelling. This structure is visible in mentors' real performance and implies that this instrument could be used to assess mentors' behaviour in addition to students' expectation from mentors. Highlights: The mentors' behaviour was a general factor at the second-order, having a direct effect on the three first-order factors. This confirmed the three-interrelated-factor structure ofmentors' behaviour identified in former studies This study showed that the scale of mentors' behaviour was useful in assess mentors' real performance. This could be useful to select good mentors and identify which behaviour is missing or weak.